2019
DOI: 10.1145/3366702
|View full text |Cite
|
Sign up to set email alerts
|

Partial Recovery of Erdðs-Rényi Graph Alignment via k-Core Alignment

Abstract: We determine information theoretic conditions under which it is possible to partially recover the alignment used to generate a pair of sparse, correlated Erdős-Rényi graphs. To prove our achievability result, we introduce the k-core alignment estimator. This estimator searches for an alignment in which the intersection of the correlated graphs using this alignment has a minimum degree of k. We prove a matching converse bound. As the number of vertices grows, recovery of the alignment for a fraction of the vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…In recent work addressing the question of δ GMP -matchability, results have been established for the R = J n , Q 1 = Q 2 = pJ n setting (see, for example, [46,40,4,18]), in the correlated stochastic blockmodel setting (see, for example, [45,38]), in the correlated heterogeneous Erdős-Renyi model (see, for example, [39,41]), and in the general R and general Q 1 = Q 2 = Q setting (see, for example, [49,42]). In the non-identically distributed model setting, the work in [14,15,16] considers R = J n , Q 1 = pJ n , and Q 2 = qJ n . In each setting, the results showed that for sufficiently dense, sufficiently correlated graphs, δ GMP -matchability is almost surely achieved.…”
Section: Graph Matchabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…In recent work addressing the question of δ GMP -matchability, results have been established for the R = J n , Q 1 = Q 2 = pJ n setting (see, for example, [46,40,4,18]), in the correlated stochastic blockmodel setting (see, for example, [45,38]), in the correlated heterogeneous Erdős-Renyi model (see, for example, [39,41]), and in the general R and general Q 1 = Q 2 = Q setting (see, for example, [49,42]). In the non-identically distributed model setting, the work in [14,15,16] considers R = J n , Q 1 = pJ n , and Q 2 = qJ n . In each setting, the results showed that for sufficiently dense, sufficiently correlated graphs, δ GMP -matchability is almost surely achieved.…”
Section: Graph Matchabilitymentioning
confidence: 99%
“…Many existing results are concerned with recovering a latent alignment present across random graph models where each of A and B have identical marginal distributions, and exciting advancements on the threshold of matchable versus unmatchable graphs have been made across many random graph settings, including: the homogeneous correlated Erdős-Renyi model (see, for example, [46,40,4,18]), the correlated stochastic blockmodel setting (see, for example, [45,38]), the ρ-correlated heterogeneous Erdős-Renyi model (see, for example, [39,41]), and in the correlated heterogeneous Erdős-Renyi model with varying edge correlations (see, for example, [49,42]). In the non-identically distributed model setting, the work in [14,15,16] provide theoretic phase transitions on matchability in the (A, B) ∼Erdős-Rényi(p,q, ) model (i.e., A ∼Erdős-Rényi(n,p), B ∼Erdős-Rényi(n,q) and the edge correlation across graphs in provided by the constant ; see Definition 2).The above results range from providing theoretic phase transitions on matchability [14,15,38] to providing nearly efficient methods for achieving matchability from an algorithmic perspective [18,4,16,22]. While they have served to establish a novel theoretical understanding of the matchability problem, in each case the transition from matchable to unmatchable graphs is defined in terms of decreasing across-graph correlation and within-graph sparsity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is the multiplex analogue of graph matchability, i.e., uncovering conditions under which oracle graph matching will recover a latent vertex alignment. Here, that alignment is represented by H being an errorful version of G[m]; see, for example, [14,20,33,32,26,21,12,11,5,13] for a litany of graph matchability results in the monoplex setting.…”
Section: Multiplex Matchabilitymentioning
confidence: 99%